73 Tia prehospital referral feasibility trial (TIER): recruitment and intervention usage. (16th April 2018) - Rees, N; Hampton, C; Bulger, J; Ali, K; Quinn, T; Ford, G; Akbari, Ashley; Ward, Matthew; Porter, Alison; Jones, C; Snooks, H
Abstract : Aim: Early specialist assessment of Transient Ischaemic Attack (TIA) can reduce the risk of stroke and death. We assessed feasibility of undertaking a multi-centre cluster randomised trial to evaluate clinical and cost effectiveness of referral of patients attended by emergency ambulance paramedic with low-risk TIA directly to specialist TIA clinic for early review. Method: We randomly allocated volunteer paramedics to intervention or control group. Intervention paramedics were trained to deliver the intervention during the patient recruitment period. Control paramedics continued to deliver care as usual. Patients with TIA were identified from hospital records. Results: Development and recruitment phases are complete, with outcome follow up ongoing. Eighty nine of 134 (66%) paramedics participated in TIER. Of 1377 patients attended by trial paramedics during the patient recruitment period, 53 (3.8%) were identified as eligible for trial inclusion. Three of 36 (8%) patients attended by intervention paramedics were referred to the TIA clinic. Of the others, only one appeared to be a missed referral; in one case there was no prehospital record of TIA; one was attended by a paramedic who was not TIER trained; one patient record was missing; all others were recorded with contraindications: FAST positive (n=13); ABCD2 score >3 (n=5); already taking warfarin (n=2); crescendo TIA (n=1) other clinical factors (n=8). Conclusion: Preliminary results indicate challenges in recruitment and low referral rates. Further analyses will focus on whether progression criteria for a definitive trial were met, and clinical outcomes from this feasibility trial. Conflict of interest: None Funding: None